1979
DOI: 10.2337/diacare.2.2.154
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Heart Disease Incidence and Cardiovascular Mortality in Busselton with Reference to Glucose and Insulin Concentrations

Abstract: In the 1966 study of the population of Busselton, Australia, blood sugar and serum insulin levels were measured one hour after an oral glucose load, in addition to the conventional cardiovascular risk factors. The six-year incidence of coronary heart disease (CHD) and the 12-yr mortality from CHD and from all cardiovascular diseases is described in relation to the initial baseline variables measured using the upper 20th percentile values (age-specific and sex-specific) to define the risk ratios. In younger sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
257
1
6

Year Published

1990
1990
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 727 publications
(274 citation statements)
references
References 0 publications
10
257
1
6
Order By: Relevance
“…Several prospective studies have also suggested this [3][4][5][6]. A recent study found normal glucose tolerant subjects with hyperinsulinaemia to have both elevated blood pressure and the lipid abnormalities often observed in glucose intolerant individuals, when compared to matched control subjects without hyperinsulinaemia [51].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several prospective studies have also suggested this [3][4][5][6]. A recent study found normal glucose tolerant subjects with hyperinsulinaemia to have both elevated blood pressure and the lipid abnormalities often observed in glucose intolerant individuals, when compared to matched control subjects without hyperinsulinaemia [51].…”
Section: Discussionmentioning
confidence: 97%
“…The precise roles of many of these factors in the pathogenesis of coronary heart disease is still not completely understood. One factor that is associated with glucose intolerance and has been implicated as being relevant to coronary heart disease from epidemiological studies [3][4][5][6] and experimental studies [7] is hyperinsulinaemia. This relationship is thought to be mediated by insulin resistance [8].…”
mentioning
confidence: 99%
“…62 In addition, we have observed that salt-sensitive subjects with essential hypertension manifest greater UAE than normotensive individuals. 63 Because hyperinsulinemia and insulin-resistance have been associated with a greater incidence of vascular disease, [64][65][66][67][68] and particularly coronary heart disease, [69][70][71] these associations could explain the greater incidence of ischemic events in patients with microalbuminuria and with salt sensitivity compared with those with normal UAE and saltresistance. Insulin levels and insulin sensitivity were not measured in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge about the relative effects of sugars on plasma insulin is important because it has been suggested that fructose increases plasma insulin without increasing plasma glucose (Reiser et al, 1987). High plasma insulin concentrations and insulin resistance are associated with increased risk of cardiovascular disease (Pyo Èra Èla È, 1978;Welborn & Wearne, 1979;Ducemetie Áre et al, 1980;DeFronzo & Ferrannini, 1991). Therefore, our purpose was to determine the effect of various doses of glucose, sucrose, fructose and white bread on plasma glucose and insulin responses in normal subjects.…”
Section: Introductionmentioning
confidence: 99%